Lacticaseibacillus rhamnosus Probio-M9 may be vertically transmitted from mother to infant during lactation based on faeces metagenomics - Lan Yang; Lai-Yu Kwok; Zhihong Sun; Heping Zhang (Food Science and Human Wellness)
Probiotics exert beneficial effects on the host. This study aimed to investigate whether maternally ingested Lacticaseibacillus rhamnosus Probio-M9 during pregnancy could access and colonize the infant gut. This study recruited one pregnant woman, who ingested Probio-M9 daily from 35 weeks of gestation to delivery. Feces of the mother-infant pair were regularly collected from one month before delivery to 6 months of infant’s age for metagenomic sequencing. Probio-M9 genomes were mappable to all infant fecal samples, suggesting the ingested probiotics could be vertically transmitted from mother to infant. Infant- or mother-specific differential metabolic pathways were found between the maternal and infant’s gut microbiome, implicating apparent differences in the intestinal metagenomic potential/function between the mother and the infant. In conclusion, maternal ingestion of Probio-M9 during the final weeks of gestation could deliver to the infant gut. The findings provided novel insights into shaping infant’s gut microbiota.